THE CORRELATION OF HEALTH PRACTICES IN PREGNANCY WITH PRENATAL ATTACHMENT AND THE EFFECTIVE FACTORS - ÖZKAN, Hava; BALABAN, Sultan (Göbeklitepe Medical Science Journal, 2021)
The study was conducted in order to determine the correlation of health practices in pregnancy with prenatal attachment and the effective factors. This research was conducted in a descriptive and relationship-seeking manner. The study was conducted with 303 pregnant women who applied to outpatient clinics of a maternity hospital in Erzurum between May 2015 and December 2015, were voluntary to participate in the study, and met the inclusion criteria of the study. The data were collected by using personal information form, Health Practice Questionnaire-II, and Prenatal Attachment Inventory. Descriptive statistics, t-test, One Way Analysis of Variance, Mann-Whitney U, Kruskall Wallis and Pearson’s Correlation Analysis were used to assess the data. It was found that while Health Practice Questionnaire-II total mean score of the pregnant women was 118.86±17.19, their Prenatal Attachment Inventory total mean score was 58.51±11.03. It was determined that characteristics such as age group, educational level, working condition, residence place, duration of marriage, educational level and working condition of their husbands, income status, family type, number of pregnancies, and planning of pregnancy affected both health practices in pregnancy and prenatal attachment level. When the correlation between Health Practice Questionnaire-II and Prenatal Attachment Inventory mean scores was examined, it was found that there was a statistically significant positive weak correlation between health practices of the pregnant women and their prenatal attachment levels (p=0.000, r=0.552). It has been determined that pregnant women have good health practices during pregnancy, and their prenatal attachment levels are moderate. As level of health practices of the pregnant women increased, prenatal attachment level also increased.